2017
DOI: 10.2106/jbjs.16.00986
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Functional Outcomes After Pantalar Dislocation

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Extreme supination and plantarflexion forces result in talar dislocation out of the ankle mortise, with disruption of the strong ligamentous attachments, which can result in an open injury [4]. Most of the literature describes talar extrusion with an anterolateral wound, which is similar to our case report [5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Extreme supination and plantarflexion forces result in talar dislocation out of the ankle mortise, with disruption of the strong ligamentous attachments, which can result in an open injury [4]. Most of the literature describes talar extrusion with an anterolateral wound, which is similar to our case report [5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 80%
“…When facing a case of open talar extrusion, we should consider the possible complications including avascular necrosis, infection, post-traumatic arthritis and the need for secondary procedures [3][4][5][6][7][8]. Hiraizumi et al concluded that the risk of avascular necrosis was the highest in the cases where no further attached soft tissue to the talus [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations